Pendekatan Komunikatif Syaikh Muhammad Mutawalli Sya’rawi: Analisis terhadap Gaya Penyampaian Dakwah kepada Jama’ah - Sukataman; Farhan Ali Ishaqi (Jurnal Selasar KPI : Referensi Media Komunikasi dan Dakwah, 2026)
This Successful dakwah (Islamic outreach) requires not only mastery of Islamic subject matter but also the ability to convey the message using language that is communicative, simple, and tailored to the audience's circumstances. Social changes in the modern era demand communication strategies capable of linking Quranic teachings to real-life situations, thereby making the dakwah message easier to understand and put into practice. This study employs a qualitative method based on a literature review focusing on the dakwah communication style of Shaikh Mutawalli Al-Sha'rawi, utilizing relevant primary and secondary sources. The findings indicate that Shaikh Mutawalli Sya’rawi employed a communicative style characterized by the use of analogies, stories, and illustrations, alongside a delivery that was dialogic, persuasive, and contextual. This approach proved effective in enhancing understanding, fostering emotional connection, and facilitating the audience's acceptance and application of the dakwah message. Thus, communicative language plays a crucial role in realizing dakwah that is effective and relevant to the needs of society.